2018
DOI: 10.1590/1806-90882017000400015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brazilian Exports of Conifer Wood Moldings Through Gravity Trade Model1

Abstract: This study aimed to analyze Brazilian exports of softwood moldings between the years 1997-2013, by means of a gravity trade model. The main explanatory variables used were GDP of Brazil, importing country´s GDP, and distance between Brazil and its trade partner. The results showed that all variables had the expected behavior. The variables´ coefficient of GDP of Brazil and the importing country's GDP presented a positive influence on trade flow of softwood moldings. The distance coefficient presented a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…In contrast to prior research on SFM by Guan, Xu, and Ip Ping Sheong [14], which explored the effects of FSC CoC certification on international trade, the studies by Chen et al [15] regarding the impact of forest certification on global timber product trade, and Klarić et al [17] who delved deeply into the benefits, motives, and shortcomings of FSC Chain of Custody certification in the wood industry, this research offers a new perspective by analysing the link between FSC CoC certification in Croatia and its wood product exports to the EU over a 21-year period, employing a unique gravity data approach. Furthermore, it integrates findings from other studies [20][21][22][23][29][30][31] that identified key macroeconomic indicators as decisive factors for export values. The use of dynamic panel data analysis further deepens this examination, emphasizing the crucial relationship between forest certification, sustainability, and market acceptance.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In contrast to prior research on SFM by Guan, Xu, and Ip Ping Sheong [14], which explored the effects of FSC CoC certification on international trade, the studies by Chen et al [15] regarding the impact of forest certification on global timber product trade, and Klarić et al [17] who delved deeply into the benefits, motives, and shortcomings of FSC Chain of Custody certification in the wood industry, this research offers a new perspective by analysing the link between FSC CoC certification in Croatia and its wood product exports to the EU over a 21-year period, employing a unique gravity data approach. Furthermore, it integrates findings from other studies [20][21][22][23][29][30][31] that identified key macroeconomic indicators as decisive factors for export values. The use of dynamic panel data analysis further deepens this examination, emphasizing the crucial relationship between forest certification, sustainability, and market acceptance.…”
Section: Introductionsupporting
confidence: 60%
“…Reviewing the literature related to macroeconomic indicators and exports, several studies [20][21][22][23][24] have shown that traditional macroeconomic indicators (such as nominal GDP, GDP per capita, unemployment, manufacturing value added, real effective exchange rate, and distance between countries) have been identified as significant and crucial determinants that lead to higher export values and stimulate export activities. For instance, Brazil's GDP variable has demonstrated a positive influence on exports of wood product, illustrating that the higher economic growth in a country theoretically corresponds to higher production levels, and consequently, a greater quantity exported [22]. Furthermore, India has been shown to have stronger trade connections with its proximate neighbours than with countries further afield [23].…”
Section: Introductionmentioning
confidence: 99%